2016
DOI: 10.1038/srep36025
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles in the blood of patients with systemic lupus erythematosus (SLE): phenotypic characterization and clinical associations

Abstract: Systemic lupus erythematosus (SLE) is a prototypic autoimmune disease characterized by circulating autoantibodies and the formation of immune complexes. In these responses, the selecting self-antigens likely derive from the remains of dead and dying cells, as well as from disturbances in clearance. During cell death/activation, microparticles (MPs) can be released to the circulation. Previous MP studies in SLE have been limited in size and differ regarding numbers and phenotypes. Therefore, to characterize MPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 55 publications
(71 reference statements)
5
76
1
Order By: Relevance
“…Studies on the use of MPs as biomarkers in SLE have assessed the total number of particles; the distribution among cell types; the presence of nucleic acids and other nuclear molecules in MPs; and the presence of IgG and IgM (Table ). Most studies have indicated that, as would be expected with inflammation, patients with SLE have higher numbers of particles in their blood compared to healthy controls . Nevertheless, Dieker et al and Crookston et al have reported similar numbers of MPs in SLE and controls while, in the study by Nielsen et al, total particle numbers were lower in SLE versus controls .…”
Section: Microparticles As Biomarkers In Slementioning
confidence: 94%
See 3 more Smart Citations
“…Studies on the use of MPs as biomarkers in SLE have assessed the total number of particles; the distribution among cell types; the presence of nucleic acids and other nuclear molecules in MPs; and the presence of IgG and IgM (Table ). Most studies have indicated that, as would be expected with inflammation, patients with SLE have higher numbers of particles in their blood compared to healthy controls . Nevertheless, Dieker et al and Crookston et al have reported similar numbers of MPs in SLE and controls while, in the study by Nielsen et al, total particle numbers were lower in SLE versus controls .…”
Section: Microparticles As Biomarkers In Slementioning
confidence: 94%
“…An important observation from these studies relates to the relative number of PS positive (+) and PS negative (−) particles. In SLE, PS‐ particles appear to constitute a much larger proportion of MPs as compared to controls . As discussed above, PS‐ particles may preferentially remain in the circulation, as PS is an important signal for removal of particles by the immune system .…”
Section: Microparticles As Biomarkers In Slementioning
confidence: 95%
See 2 more Smart Citations
“…Although microparticles have been described in systemic lupus erythematous [17,18], they appear to be unrelated to the microcomplexes described herein because they are too large (0.1-1.0 μm) to pass through 10 kDa cut-off ultrafilters.…”
Section: Discussionmentioning
confidence: 85%